Method for inhibiting transverse cracks of flange of niobium-containing steel casting blank

By using a low-carbon, high-manganese system and Nb-Ti composite microalloying, combined with zoned cooling and the use of lithium-containing protective slag in high-alkalinity peritectic steel, the composition and cooling process of niobium-containing steel billets were optimized, solving the problem of transverse flange cracks in niobium-containing steel billets and achieving a highly efficient crack suppression effect, which is suitable for the production of high-end steel grades.

CN120905582APending Publication Date: 2025-11-07SHANDONG IRON & STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511123891.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-12
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

During continuous casting, niobium-containing steel billets are prone to expansion of the second brittle temperature range due to the precipitation of carbonitrides along the austenite grain boundaries. Transverse cracks are particularly likely to occur in the flange region of complex cross-sections of irregular billets. Existing control methods suffer from problems such as large fluctuations in the liquid level of the crystallizer, unreasonable cooling water distribution, single composition design, and crude control of straightening temperature, resulting in a high incidence of transverse cracks.

Method used

By employing a low-carbon, high-manganese system combined with Nb-Ti composite microalloying, and controlling the cooling temperature in five zones and gradient cooling, along with high-alkalinity peritectic steel lithium-containing protective slag and intelligent stopper rod control, the composition design and cooling process are optimized to achieve synergistic effects of composition design, liquid level fluctuation regulation, and gradient cooling.

Benefits of technology

It effectively suppresses the generation of transverse cracks in the flanges of niobium-containing steel billets, improves billet quality, is suitable for the production of high-end steel grades, promotes the industry towards high quality and intelligent development, and has broad industrial application prospects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for inhibiting transverse cracks of a niobium-containing steel casting blank flange, and relates to the technical field of metallurgy continuous casting. According to the method, a low-carbon high-manganese system is combined with Nb-Ti composite microalloying to adjust chemical components of a niobium-containing steel casting blank, in the continuous casting process, gradient cooling is cooperatively achieved by controlling the cooling temperature in five zones and controlling the temperature gradient of a flange zone to be smaller than or equal to 20 DEG C / m, and meanwhile the fluctuation range of the liquid level in a crystallizer is controlled; component design, liquid level fluctuation regulation and control and gradient cooling cooperation are achieved, and efficient inhibition of niobium-containing casting blank flange transverse cracks is achieved. The method has remarkable advantages in the field of transverse crack inhibition of the niobium-containing steel special-shaped blank, and has a wide industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of metallurgical continuous casting, in particular to a method for inhibiting the transverse cracks of the flange of a niobium-containing steel casting blank. BACKGROUND

[0002] The niobium-containing steel is widely used in the engineering structure field due to the Nb(C, N) precipitation strengthening, but the high-temperature plasticity thereof is low, and the second brittle temperature interval is easily expanded due to the carbonitride precipitation along the austenite grain boundary during the continuous casting process. In particular, the transverse cracks are easily caused in the flange region of the beam blank due to the uneven cooling and the stress concentration of the straightening. The transverse cracks are of different sizes and depths, and the micro-cracks are extremely likely to be further developed in the subsequent heating and rolling process, causing crack defects and affecting the quality of the casting blank.

[0003] In the prior art, the generation of the transverse cracks of the niobium-containing steel casting blank is reduced by optimizing and controlling the continuous casting process parameters of the niobium-containing steel casting blank, such as the improvement of the molten steel composition, the continuous casting cooling characteristics, the optimization of the protective slag, and the like, so as to improve the quality of the casting blank. The traditional method for controlling the transverse cracks of the niobium-containing steel casting blank has the following defects: 1. The liquid surface of the crystallizer fluctuates greatly, causing the unstable flow of the molten steel and aggravating the uneven thickness of the blank shell; 2. The cold water distribution is unreasonable (the cold water distribution ratio is 1.0-1.2 L / kg), the cooling intensity is not optimized according to the cross-section characteristics of the beam blank, and the cooling rate of the flange region is too fast; 3. The molten steel composition of the continuous casting blank is single, the interaction of the elements such as Nb, Al and N is not effectively balanced, and the risk of grain boundary embrittlement is high; 4. The straightening temperature control is rough, the second brittle temperature interval is not avoided by local heating, and the crack occurrence rate is more than 0.15%. These defects commonly exist in different links of the same continuous casting process, which is a systematic problem. Therefore, it is necessary to improve the defects of the method for controlling the transverse cracks in a systematic and collaborative manner to inhibit the generation of the transverse cracks of the flange of the niobium-containing steel casting blank. SUMMARY

[0004] In view of the above prior art, the purpose of the present application is to provide a method for inhibiting the transverse cracks of the flange of a niobium-containing steel casting blank. The present application adopts a low-carbon high-manganese system combined with Nb-Ti composite micro-alloying to realize the composition adjustment of the niobium-containing steel, optimizes the beam blank stopper control strategy and the cooling process of the continuous casting process, realizes the synergy of the composition design, the stopper dynamic regulation and the gradient cooling, and realizes the efficient inhibition of the transverse cracks of the flange of the niobium-containing beam blank.

[0005] In order to achieve the above purpose, the present application adopts the following technical solutions: The present application provides a method for inhibiting the transverse cracks of the flange of a niobium-containing steel casting blank, comprising the following steps: Adjusting the chemical composition of the flange of the niobium-containing steel casting blank, so that the flange of the niobium-containing steel casting blank comprises the following components in mass percentage: C 0.08%-0.12%, Mn 1.4%-1.5%, Nb 0.03%-0.04%, Ti 0.008%-0.018%; The production process comprises: pretreatment desulphurization of molten iron, converter smelting, LF refining and continuous casting, to obtain the flange of the niobium-containing steel casting blank; wherein, The continuous casting process: the liquid level fluctuation range of the crystallizer is stabilized within ±3mm, the high basicity peritectic steel lithium-containing protective slag is used; the total specific water quantity of the water distribution system of the secondary cooling is controlled to be 0.6-0.8L / kg, the weak cooling mode is used in the flange corresponding secondary cooling zone, the cooling temperature is controlled in five zones, which are: zone one 50-55%, zone two 25-27%, zone three 20-25%, zone four 15-22%, zone five 10-15%; the specific water quantity of the inner arc is 15-20% lower than that of the outer arc, the nozzle water quantity is adjusted, so that the temperature gradient of the flange area is ≤20℃ / m; the secondary cooling water temperature is controlled to be 30-35℃; the constant casting speed 0.95m / min is used in cooperation with the low cooling rate ≤1.5℃ / s, so that the casting blank surface temperature is kept ≥920℃ in the straightening section, the tundish temperature is dynamically matched with the casting speed, and the casting speed is reduced by 0.02m / min for every 5℃ increase of the temperature.

[0006] As preferred, the high basicity peritectic steel lithium-containing protective slag comprises the following mass fractions of components: SiO222.03-24.06%, Al2O312.03-12.24%, Fe2O31.09-1.15%, CaO 34.47-34.99%, R 1.56-1.58%, Na2O 0.50-0.53%, F 4.08-4.10%, Li2O 0.4-0.45%, C 15.34-15.55%, H2O 0.33-0.34%; the melting point thereof is 1275-1276℃, the melting speed is 43-44s, the bulk density is 0.71-0.73g / cm³, and the viscosity is 0.56-0.59Pa.S.

[0007] As preferred, the molten iron pretreatment desulphurization is to S≤0.008%, and the slag skimming rate is ≥95%.

[0008] As preferred, in the converter smelting process, the end point C content is controlled to be 0.05%-0.07%; the oxygen lance gun position adopts a 'high-high-low' oxygen lance gun position control mode, the initial high gun position range is 1800mm-1850mm, the medium high gun position range is 1450mm-1600mm, and the late low gun position range is 1000mm-1200mm; the end point low gun position time is controlled to be greater than or equal to 60s; the oxygen pressure in the oxygen blowing process is controlled to be 0.7MPa-1.0MPa; metal manganese, silicon iron, niobium iron and nickel plate are used for alloying, and are added uniformly when the molten steel is discharged to 1 / 4, and are added completely when the molten steel is discharged to 3 / 4, the alloy is added to the impact area of the steel flow, and the steel tapping time is greater than or equal to 3min, and the steel tapping temperature is 1630℃-1650℃.

[0009] As preferred, in the LF refining process, argon stirring is used throughout the process, the argon flow is 100-200L / min, and the argon purity is 99.99%; after the carbon additive is added, the argon flow is adjusted to 800-1000L / min, and argon blowing is performed for 2min-5min; the entry station temperature is 1554℃-1574℃, and the exit station temperature is 1560℃-1578℃; the soft argon blowing time is greater than 12min, the calcium wire is fed 80-120m / furnace before soft argon blowing, and the refining period is not less than 45min.

[0010] As preferred, in the continuous casting process, the long nozzle of the ladle adopts a sealing ring and argon sealing protection, the argon flow of the ladle is controlled to be 100-150L / min; the immersion nozzle of the tundish is controlled to have an insertion depth of 70-80mm, and the superheat degree of the molten steel in the tundish is 15-28℃; the water volume control range of the crystallizer is adjusted to be: the inner and outer arcs are 1800-1850L / min, and the side arc is 1100-1200L / min; the water temperature of the crystallizer is controlled to be 38-42℃; and the crystallizer structure adopts a curved copper plate design, and the uniformity of the heat flow density is increased by 20%.

[0011] As preferred, in the continuous casting process, the thickness of the high-basicity peritectic steel lithium-containing protective slag in the crystallizer is 50-60mm, and the thickness of the liquid slag layer is 4-6mm.

[0012] The beneficial effects of the present application are: 1. The present application adopts a low-carbon high-manganese system combined with Nb-Ti composite micro-alloying to realize the adjustment of the chemical composition of the niobium-containing steel casting blank, in the continuous casting process, the cooling temperature is controlled in five zones, the temperature gradient of the flange area is controlled to be ≤20℃ / m, the gradient cooling is realized at the same time, the liquid surface fluctuation range in the crystallizer is controlled, the composition design, liquid surface fluctuation control and gradient cooling are coordinated, and the high-efficiency inhibition of the niobium-containing casting blank flange transverse crack is realized.

[0013] The application can realize significant advantages in the field of inhibiting transverse cracks of Nb-containing steel beam blanks, is especially suitable for high-end steel production, promotes the development of the industry towards high quality and intelligence, and has wide industrial application prospects in the future by intelligent upgrading and multi-technology cooperation to further improve control precision and universality.

[0014] 2. Different from the end gun position time period and large fluctuation in the traditional process, the application adopts a "high-high-low" three-stage gun position control (initial stage-mid stage-late stage) in the converter smelting process. By controlling the low end gun position to be greater than or equal to 60s, the problem of grain boundary embrittlement caused by high Nb(C,N) precipitation sensitivity of Nb-containing steel and rough end control is solved.

[0015] 3. The application also adjusts the proportion of each component of the protective slag and the unique addition of lithium element. The suitable component proportion makes the physical properties of the protective slag such as melting point, melting rate, bulk density and viscosity reach an ideal state, forms a uniform and stable slag film on the surface of the casting blank, effectively isolates air and reduces the oxidation of the surface of the casting blank; the good slag film can improve the heat transfer in the mold, reduce the surface temperature gradient of the casting blank and reduce the thermal stress concentration, thereby inhibiting the transverse cracks. The lithium element enhances the key performance of the protective slag, such as improving the lubricity and uniformity of the slag film, and further reducing the friction and thermal stress between the casting blank and the mold wall. DETAILED DESCRIPTION

[0016] It should be noted that the following detailed description is exemplary and is intended to provide further explanation of the present application. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.

[0017] In order for those skilled in the art to more clearly understand the technical solutions of the present application, the technical solutions of the present application will be described in detail below with specific embodiments.

[0018] In the prior art, the existing control method of transverse cracks of Nb-containing steel casting blanks has defects such as large liquid level fluctuation in the mold, unreasonable cold water distribution, single component design of Nb-containing steel casting blanks and rough straightening temperature control during continuous casting.

[0019] Based on this, the application provides a method for controlling the transverse cracks of the flanges of Nb-containing steel casting blanks. Specifically, The components of the Nb-containing steel slab flange are adjusted, so that the Nb-containing steel slab flange comprises the following mass percentages of components: C 0.08%-0.12%, Mn 1.4%-1.5%, Nb 0.03%-0.04%, Ti 0.008%-0.018%. In the above components, C, Mn, Nb, Ti, S, and N are key elements affecting transverse cracks, and the specific effects are as follows: Carbon (C): If the content is too high (>0.12%), it will increase the hardening tendency of the steel, and hard and brittle structures such as martensite are easy to form during cooling, which increases the brittleness of the grain boundary. If the content is too low (<0.08%), the high-temperature strength of the steel may be reduced, and the stress concentration of the slab shell during straightening cannot be inhibited. By controlling the C content to be 0.08%-0.12%, the toughness and strength can be balanced, and the crack risk can be reduced. Manganese (Mn): As a strong austenite forming element, Mn can expand the austenite zone and reduce the brittleness transition temperature of the steel. In the present application, Mn is controlled to be 1.4%-1.5%, which can improve the high-temperature plasticity of the steel and inhibit stress cracks caused by uneven cooling. However, if the content is too high, S forms MnS inclusions, which increases the crack source. Niobium (Nb): Nb is easy to combine with C and N to form Nb (C, N) precipitates. If the precipitation amount is too much (>0.04%) or continuously distributed at the austenite grain boundary, it will significantly reduce the grain boundary bonding force, causing the high-temperature brittle zone to expand, especially in the unevenly cooled areas such as flanges, which can easily cause cracks. In the present application, Nb is controlled to be 0.03%-0.04%, and Ti is used for complex micro-alloying to inhibit its harmful precipitation. Titanium (Ti): Ti has a stronger affinity with N than Nb, and preferentially forms TiN, which can reduce the combination of Nb and N and avoid the excessive precipitation of Nb (C, N) at the grain boundary. In the present application, Ti is controlled to be 0.008%-0.018%, which can effectively refine the grain, improve the grain boundary state, and reduce the transverse crack occurrence rate. Sulfur (S): S is a harmful element that easily forms low-melting-point FeS at the grain boundary, causing high-temperature brittleness and exacerbating crack propagation. In the present application, the molten iron is pretreated to reduce S to ≤0.008%, reducing the risk of thermal brittleness. Nitrogen (N): Free N is easy to form nitrides with Nb and Al, and uneven precipitation can cause grain boundary embrittlement. In the present application, N is controlled to be ≤0.012%, and the preferential combination of Ti avoids the harmful interaction of N and Nb. These key elements directly or indirectly affect the formation and propagation of transverse cracks by affecting the high-temperature plasticity of the steel, the grain boundary state, the distribution of precipitates, and the thermal brittleness sensitivity, so the control of their content is one of the core means to inhibit cracks.

[0020] In the converter smelting process, a "high-high-low" three-stage gun position control (initial stage → middle stage → late stage) is adopted. Among them, the initial high gun position range is 1800-1850mm, which can ensure rapid slagging after blowing and avoid splashing; the middle high gun position range is 1450-1600mm, which can adjust the gun position to optimize the decarburization reaction and control the FeO in the slag; the late low gun position range is 1000-1200mm, which reduces the gun position near the end point, strengthens the molten bath stirring, and promotes the mixing and temperature uniformity of steel slag. The "end point low gun position time" is the core parameter in the late operation, which refers to the duration from the start of the low gun position (1000-1200mm) to the end of smelting. Unlike the traditional process (short and fluctuating end point low gun position time), the present application solves the problem of grain boundary embrittlement of niobium-containing steel caused by high Nb (C, N) precipitation sensitivity and rough end point control by forcing the end point low gun position to be ≥60s.

[0021] In the LF refining process, the calcium feeding line is 80-120 meters per furnace, which can indirectly control the nitride morphology. Calcium can react with impurities such as sulfur and oxygen in the steel to change the properties of inclusions, thereby affecting the precipitation environment of nitrides, promoting the preferential precipitation of TiN, reducing the continuous distribution of Nb (C, N) at the grain boundary, and achieving nitride morphology control. And through the whole process of bottom blowing argon stirring, the argon flow is 100-200L / min, the argon purity is 99.99%, which can promote the uniformity of the composition of the molten steel, and is beneficial to the floating removal of inclusions. After the addition of recarburizer, adjust the argon flow to 800-1000L / min, blow argon for 2-5min, which can further strengthen the stirring effect, making it easier for inclusions to aggregate and grow. Soft blowing argon time > 12min, calcium feeding line 80-120 meters per furnace before soft blowing argon, calcium reacts with inclusions in molten steel to make inclusions spheroidized, average equivalent diameter <6μm, realizing inclusion modification.

[0022] In the continuous casting process, the liquid surface fluctuation range of the crystallizer and the cooling method are optimized. Among them, the core goal of gradient cooling is to finally make the temperature gradient of the flange area ≤20℃ / m through five-zone control and nozzle water quantity adjustment, so as to avoid the concentration of thermal stress caused by excessive temperature gradient. Five-zone control is a spatial means to realize gradient cooling. Five cooling zones are divided along the traveling direction of the casting blank, and the cooling intensity of each zone is set according to the casting blank temperature, thickness and heat dissipation demand of the region. Through the step-by-step decrease of the cooling intensity of each zone, the proportion from zone one to zone five is sequentially reduced, forming the basis for temperature gradient control along the length direction of the casting blank. First, the initial water quantity of each zone is calculated according to the proportion of the five zones, combined with the total specific water quantity of 0.6-0.8L / kg; considering the difference between the inner arc and the outer arc, the specific water quantity of the inner arc is 15-20% lower than that of the outer arc, and the difference is realized by separately adjusting the valve opening of the inner arc and the outer arc nozzle. For example, when the opening of the outer arc nozzle is too large, the inner arc valve is adjusted to reduce the water quantity of the inner arc in proportion; when the gradient is too large, the nozzle flow of the region is appropriately reduced to slow down the cooling speed; when the gradient is too small, the flow is appropriately increased to control the water temperature of the secondary cooling to be stable at 30-35℃, so as to avoid the influence of water temperature fluctuation on the cooling efficiency and ensure the control accuracy of the water quantity adjustment on the temperature gradient. In summary, gradient cooling is a collaborative control strategy that realizes the temperature gradient of the flange area ≤20℃ / m through the spatial cooling intensity distribution of five zones, combined with the differential adjustment of the inner arc and the outer arc and the real-time temperature gradient feedback. In addition, the composition and proportion of the protective slag are also optimized in the continuous casting process. Through diligent and less addition, the liquid slag layer thickness is stabilized at 4-6mm. From the start of continuous casting to the end of casting, the molten steel surface in the crystallizer is always covered with protective slag to avoid direct contact of molten steel with air, thereby avoiding secondary oxidation, and at the same time, the thickness of the protective slag is maintained at 50-60mm to ensure the uniformity of lubrication and heat transfer, thereby indirectly inhibiting the flange transverse crack.

[0023] In summary, the present application realizes the generation of flange transverse cracks of niobium-containing steel casting blank through the collaborative design of the composition of the flange of niobium-containing steel casting blank, the control of the liquid surface fluctuation range of the crystallizer and the gradient cooling.

[0024] The experimental materials used in the embodiments of the present application are all conventional experimental materials in the art and can be purchased through commercial channels.

[0025] Embodiment 1: The flange of the niobium-containing steel casting blank in this embodiment is S355NL-H1 alloy structural high-strength steel special-shaped blank (575×450×110mm).

[0026] 1. The chemical composition of the flange of the niobium-containing steel casting blank is (in mass percent): C: 0.09%, Si: 0.20%, Mn 1.45%, P 0.018%, S 0.005%, Ni 0.20%, Nb 0.035%, Ti 0.015%, Al 0.020%, N≤0.012%, CEV / %≤0.39%, residual elements Cu≤0.55%, Cr≤0.30%, Mo≤0.10%, the balance being iron and unavoidable impurities; 2. Production process: (1) Pretreatment desulfurization: the molten iron is pretreated at 1360°C, so that the pretreated molten iron S≤0.008%, and the slagging rate≥95%; (2) Converter smelting: the slag on the surface of the molten iron is cleaned after desulfurization, the iron-steel ratio is 0.92, the final C content is 0.06%, the final slag basicity is 3.2, S355NL-H1 is deoxidized by aluminum-manganese iron, the aluminum-manganese iron addition amount is 2.0 kg / t of steel, and 5 kg / t of top lime is added after tapping. The "high-high-low" oxygen lance position mode (initial-middle-late) is adopted, the initial position is 1825 mm, the middle position is 1475 mm, and the final position is 1100 mm, the final low grab position time is≥60 s, the process oxygen pressure is controlled at 0.85 Mpa, the slag is well sublimated and penetrated throughout the process, and the final pressing time is≮1 minute. Metal manganese, ferrosilicon, niobium iron, and nickel plate are used for alloying, the alloy is added uniformly when the molten steel is out to 1 / 4, and the alloy is added completely when the molten steel is out to 3 / 4, the alloy is added to the steel flow impact area, the tapping time is≥3 min, and the tapping temperature is 1640°C.

[0027] (3) LF refining: whole process bottom argon stirring, argon flow 150 L / min, argon purity 99.99%; after the addition of carbonizer, adjust the argon flow to 900 L / min, blow for 3 min; the inlet temperature is 1564°C, and the outlet temperature is 1570°C before the outlet, soft blowing is used to ensure that the inclusions float, and the soft blowing time is≥12 min before the outlet, 120 meters of calcium wire is fed per furnace before soft blowing, and the refining cycle is 46 min (including soft blowing).

[0028] (4) Continuous casting: The intelligent control system of hydraulic servo driven stopper rod is adopted, and the core parameters in the process are as follows: the system response time is 45 ms (<50 ms), the steel flow deviation is stably controlled at 1.2% (≤1.5%) when the pulling speed fluctuation is ±0.05 m / min; according to the real-time feedback of the mold liquid level, the Cs-137 isotope detector is used for monitoring, and the stopper opening degree is adjusted through the PLC closed loop control when the liquid level deviates from the set value ±2 mm, the servo cylinder displacement sensor precision is ±0.01 mm, the stopper position is immediately adjusted, and the liquid level fluctuation is strictly controlled within ±3 mm; the servo proportional valve frequency width is 40 Hz, the flow characteristic linearity is ±0.8%, the position pressure double feedback of the double-acting hydraulic cylinder is matched, the stepless adjustment of the stopper opening degree is realized, the opening degree range is 30%-70%, and the opening degree is dynamically matched according to the pulling speed 0.95 m / min. The mold structure adopts the curved copper plate design, and the uniformity of the wide surface heat flow density is improved by 20%.

[0029] A high basicity peritectic steel lithium-containing mold powder is used, which comprises the following components in mass fraction: SiO2 23.05%, Al2O3 12.13%, Fe2O3 1.12%, CaO 34.69%, R 1.57%, Na2O 0.52%, F 4.09%, Li2O 0.43%, C 15.42%, H2O 0.33%; the melting point thereof is 1276℃, the melting speed is 43s, the bulk density is 0.72g / cm3, and the viscosity is 0.57Pa.S; five fixed adding points are uniformly arranged along the periphery of the upper mouth of the crystallizer, so as to ensure that the mold powder can uniformly cover the molten steel surface in the crystallizer and avoid local accumulation and exposure. According to the pulling speed and the melting speed of the mold powder, the interval of each batch is usually 2min. When the pulling speed is stable, the fixed interval is maintained, so as to ensure that the liquid slag layer thickness is stably controlled at 5mm, the adding amount of each adding point in each batch is 0.7kg, the total adding amount is 3.5kg / batch, and the adding amount is adjusted according to the cross-sectional size of the crystallizer. The mold powder is gently put into the mold by using a small spoon during the adding process. From the beginning of continuous casting to the end of casting, the above steps are continuously operated, so as to ensure that the molten steel surface in the crystallizer is always covered by the mold powder, avoid the direct contact between the molten steel and the air to cause secondary oxidation, maintain the thickness of the mold powder at 55mm, and indirectly inhibit the transverse cracks of the flange; The sealing ring + argon sealing protection is adopted for the long nozzle of the ladle, the argon flow of the ladle is 120L / min, the immersion nozzle of the tundish is inserted to a depth of 75mm, the superheat degree of the molten steel in the tundish is controlled at 23℃, the water volume control range of the BB1 cross section (575*450*110mm) of the crystallizer is adjusted as follows: the inner and outer arcs are 1820L / min, the side arcs are 1180L / min, the amplitude is ±3mm, and the water temperature of the crystallizer is controlled at 40℃. The total water quantity of the secondary cooling water distribution system was 0.6 L / kg, and was controlled in five zones (51% in the first zone, 26% in the second zone, 23% in the third zone, 17% in the fourth zone, and 12% in the fifth zone), and the inner arc water quantity was 18% lower than the outer arc water quantity. In combination with the slab surface temperature field, the nozzle water quantity was adjusted in real time to make the temperature gradient of the flange region ≤20 ℃ / m; the secondary cooling water temperature was controlled at 32 ℃, and a constant casting speed of 0.95 m / min was used to cooperate with a low cooling rate of ≤1.5 ℃ / s to make the flange temperature at the straightening section 950 ℃; the tundish molten steel weight was 35 t, and the tundish molten steel temperature was 1537 ℃.

[0030] 3. Performance: The method was used in the BB1 section of the beam blank caster, and 10 heats were produced in total, with a total of 1450 t. The nitrogen content of the 10 heats of crystallizer gas samples was the highest value of 26 ppm, the lowest value of 20 ppm, the average value of 23 ppm, the oxygen content was the highest value of 25 ppm, the lowest value of 17 ppm, and the average value of 20 ppm.

[0031] All the slabs were cooled and finished on the ground, and the finishing parts included the inner side of the flange and the web. There were 4 subcutaneous longitudinal cracks in the web, and the length of the web longitudinal crack was about 30-60 mm. There was no transverse crack in the flange skinning finishing inspection.

[0032] The mechanical and process properties of the rolled material were detected, the rolled material specification was HE240A, the average value of the upper yield strength was 375 MPa, the average value of the tensile strength was 365 MPa, the average value of the elongation after fracture was 26%, and the average value of the impact energy at -50 ℃ was 34 J, all of which met the requirements.

[0033] Example 2: The Nb-containing steel slab flange in this example was a S355MLO-2 low alloy high strength structural steel beam blank (575x450x110 mm).

[0034] 1. The chemical components of the Nb-containing steel slab flange were (in mass percent): C 0.08%, Si 0.20%, Mn 1.4%, P 0.012%, S 0.006%, Ni 0.2%, Nb 0.032%, Ti 0.010%, Al 0.022%, CEV / % ≤0.39, residual elements Cu ≤0.30%, Cr ≤0.25%, Mo ≤0.08%, N ≤0.012%, B ≤0.0008%, As ≤0.03%, Sb ≤0.010%, Sn ≤0.020%, Pb ≤0.010%, Bi ≤0.010%, Ca ≤0.005%, the balance being iron and unavoidable impurities.

[0035] 2. Production process: (1) Pretreatment desulfurization: The molten iron was desulfurized at 1370 ℃ to make the pretreated molten iron S ≤0.008%, and the slagging rate ≥95%. (2) Converter smelting: after desulphurization of the treated hot metal, the slag on the surface of the hot metal is removed, the iron to steel ratio is 0.92, the end point C content is 0.08%, the final slag basicity is 3.5, S355MLO-2 is deoxidized by aluminum-manganese iron, the aluminum-manganese iron addition amount is 2.2 kg / t of steel, and 4 kg / t of top lime is added after tapping. In this process, a "high-high-low" oxygen lance position mode (initial-middle-late) is adopted, the initial position is 1800 mm, the middle position is 1450 mm, and the end position is 1000 mm, the end position low grabbing time is ≥60 s, the process oxygen pressure is controlled at 0.70 Mpa, the slag is well sublimated and penetrated throughout the process, and the end position pressing time is > 1 minute. Metal manganese, silicon iron, niobium iron and nickel plate are used for alloying, the alloy is uniformly added when the molten steel is 1 / 4 out, and the alloy is added completely when the molten steel is 3 / 4 out, the alloy is added to the impact area of the steel stream, the tapping time is ≥3 min, and the tapping temperature is 1630℃.

[0036] (3) LF refining: argon stirring is used throughout the process, the argon flow is 100 L / min, and the argon purity is 99.99%; after the carbon additive is added, the argon flow is adjusted to 800 L / min, and argon blowing is performed for 2 min; the entry temperature is 1554℃, a small pressure soft blowing is used before the exit to ensure that the inclusions float up, and the exit temperature is 1560℃; the soft blowing argon time is ensured to be > 12 min, 100 meters of calcium wire is fed per furnace before soft blowing argon, and the refining cycle is 45 min (including soft blowing).

[0037] (4) Continuous casting: an intelligent control system of hydraulic servo driven stopper is used, and the core parameters in this process are as follows: the system response time is 48 ms, the flow deviation is controlled to be 1.3% when the pulling speed is maintained at 0.95 m / min; when the intermediate ladle molten steel temperature fluctuation causes the pulling speed to be adjusted by ±0.03 m / min, the flow deviation is still ≤1.4%; the stopper opening adjustment step is corrected by 0.1 mm / once through self-adaptive algorithm, when the crystallizer liquid level fluctuates by ±2.5 mm, it is restored to ±1 mm within 1.5 s, and the maximum liquid level fluctuation is ≤±3 mm throughout the process; the servo cylinder working pressure is 12 MPa, and the stopper idle stroke is 0.8 mm.

[0038] The high basicity peritectic steel lithium-containing protective slag comprises the following components in mass fraction: SiO2 23.03%, Al2O3 12.03%, Fe2O3 1.09%, CaO 34.47%, R 1.56%, Na2O 0.50%, F 4.08%, Li2O 0.4%, C 15.34%, H2O 0.34%; the melting point is 1275℃, the melting speed is 43s, the volume weight is 0.71g / cm3, and the viscosity is 0.56Pa.S; five fixed adding points are evenly arranged along the upper edge of the crystallizer to ensure that the protective slag can evenly cover the liquid steel surface in the crystallizer and avoid local accumulation and exposure. According to the casting speed and the melting speed of the protective slag, the interval of each batch is usually 3min. When the casting speed is stable, the fixed interval is maintained to ensure that the liquid slag layer thickness is stable at 4mm, the adding amount of each adding point is 0.7kg per batch, and the total adding amount is 3.5kg per batch. The specific adding amount is adjusted according to the cross-sectional size of the crystallizer, and the adding is carried out slowly and gently with a small spoon. From the start of continuous casting to the end of casting, the above steps are continuously operated to ensure that the liquid steel surface in the crystallizer is always covered with protective slag to avoid direct contact of the molten steel with air to cause secondary oxidation, while maintaining the thickness of the protective slag at 50mm to ensure uniformity of lubrication and heat transfer and indirectly inhibit the transverse crack of the flange; The long nozzle of the ladle is protected by a sealing ring and argon sealing, the argon flow rate of the ladle is 120L / min, the immersion nozzle of the tundish is inserted to a depth of 70mm, the superheat degree of the molten steel in the tundish is controlled at 15℃, and the water flow rate control range of the BB1 section (575*450*110mm) of the crystallizer is adjusted as follows: the inner and outer arcs are 1820L / min, the side arcs are 1180L / min, the amplitude is ±3mm, and the water temperature of the crystallizer is controlled at 38℃; The total specific water flow rate of the secondary cooling water distribution system is 0.7L / kg, which is controlled in five zones (Zone 1: 53%, Zone 2: 29%, Zone 3: 26%, Zone 4: 20%, and Zone 5: 18%), the specific water flow rate of the inner arc is 15% lower than that of the outer arc, the water flow rate of the nozzle is adjusted in real time in combination with the surface temperature field of the cast blank to make the temperature gradient of the flange region ≤20℃ / m, the secondary cooling water temperature is controlled at 30℃, the constant casting speed is 0.95m / min, and the low cooling rate is ≤1.5℃ / s to make the flange temperature at the straightening section 970℃, and the molten steel weight in the tundish is 35t, and the molten steel temperature in the tundish is 1538℃.

[0039] 3. Performance: The method is used in 8 heats and 1080t in the BB1 section of the profiled blank continuous casting machine, the nitrogen content of the gas samples of the crystallizers of the 8 heats is taken, the maximum value is 30ppm, the minimum value is 25ppm, the average value is 26ppm, the oxygen content is 28ppm, the minimum value is 20ppm, and the average value is 25ppm.

[0040] All the cast slabs were floor slow cooling and finishing, the finishing position included the inner side of flange, the web had 6 longitudinal cracks, the length of the longitudinal cracks was about 30-60mm, the flange skinning finishing inspection had no transverse cracks.

[0041] According to the mechanical and process properties of the rolled material, the rolled material specification H500*200*10*16mm, the average yield strength was 375Mpa, the average tensile strength was 560Mpa, the average elongation after fracture was 26%, the average impact energy at-40℃ was 55J, all met the requirements.

[0042] Example 3 The flange of the Nb-containing steel cast slab in this example was SM490YB-2 offshore oil platform structure steel contoured bloom (575x450x110mm).

[0043] 1. The chemical components of the flange of the Nb-containing steel cast slab were (in mass percent): C 0.10%, Si 0.20%, Mn 1.45%, P 0.010%, S 0.005%, Ni 0.20%, Nb 0.035%, Ti 0.018%, Al 0.020%, CEV / %≤0.41, residual elements Cu≤0.30%, Cr≤0.30%, Mo≤0.30%, the balance being iron and unavoidable impurities.

[0044] 2. Production process: (1) Pretreatment desulfurization: the molten iron was pretreated at 1370℃, so that the S content of the pretreated molten iron was ≤0.008%, and the slagging rate was ≥95%; (2) Converter smelting: the slag on the surface of the molten iron was removed after desulfurization, the iron-steel ratio was 0.92, the C content at the end point was 0.08%, the final slag basicity was 3.4, SM490YB-2 was deoxidized by aluminum-manganese iron, the aluminum-manganese iron addition amount was 2.5kg / t of steel, and 4kg / t of top lime was added after tapping. The "high-high-low" oxygen lance position mode (initial-middle-late) was adopted, the initial position was 1850mm, the middle position was 1600mm, and the end point was 1200mm, the end point low grab position time was ≥60s, the process oxygen pressure was controlled at 1.0Mpa, the slag was well sublimated and penetrated throughout the process, and the end point pressing time was >1 minute. Metal manganese, ferrosilicon, niobium iron, and nickel plate were used for alloying, the alloying was started when the molten steel was out to 1 / 4, and was completed when the molten steel was out to 3 / 4, the alloying was added to the steel flow impact area, the tapping time was ≥3min, and the tapping temperature was 1650℃.

[0045] (3) LF refining: full-course bottom argon stirring, argon flow rate 200 L / min, argon purity 99.99%; after the addition of the carburizer, adjust the argon flow rate to 1000 L / min, and blow argon for 5 min; the entry station temperature is 1574°C, and a small pressure soft blowing is used before the exit station to ensure that the inclusions float up, and the exit station temperature is 1578°C; the soft blowing argon time during the refining is > 12 min, 120 meters of calcium wire is fed per furnace before the soft blowing argon, and the refining cycle is 45 min (including soft blowing).

[0046] (4) Continuous casting: an intelligent control system of a hydraulic servo driven stopper is used, and the stopper control uses a "pulling speed-flow-liquid level" three-parameter linkage adjustment. The core parameters in the process are as follows: the system response time is 42 ms, the flow deviation is stabilized at 1.0% when the pulling speed is 0.95 m / min; when the tundish molten steel weight decreases from 35 t to 25 t, the stopper opening is dynamically increased from 45% to 55% through a pre-set flow compensation model, to ensure that the flow deviation is ≤1.5%; the stopper opening adjustment frequency and the mold liquid level detection frequency are synchronized at 50 Hz, and the liquid level fluctuation is controlled within ±2.8 mm; when it is detected that the nozzle water fluctuation causes the liquid level to deviate from ±3 mm instantaneously, the system triggers a fast response mode, and the stopper opening is compensated and adjusted within 50 ms, to avoid the crack inducement.

[0047] A high basicity peritectic steel lithium-containing protective slag is used, which comprises the following components in mass fraction: SiO224.06%, Al2O312.24%, Fe2O31.15%, CaO 34.99%, R 1.58%, Na2O 0.53%, F 4.10%, Li2O 0.45%, C 15.55%, H2O 0.34%; the melting point thereof is 1276°C, the melting rate is 44 s, the bulk density is 0.73 g / cm³, and the viscosity is 0.59 Pa.S; five fixed addition points are uniformly set along the upper edge of the mold, to ensure that the protective slag can uniformly cover the molten steel surface in the mold and avoid local accumulation and exposure. According to the pulling speed and the protective slag melting rate, the interval of each batch is usually 3 min. When the pulling speed is stable, the fixed interval is maintained, to ensure that the liquid slag layer thickness is stable at 6 mm, the addition amount of each batch at each addition point is 0.7 kg, and the total addition amount is 3.5 kg / batch. The specific addition amount is adjusted according to the mold cross-sectional size, and the addition is carried out gently with a small spoon. From the start of continuous casting to the end of casting, the above steps are continuously operated, to ensure that the molten steel surface in the mold is always covered with the protective slag, to avoid the direct contact of the molten steel with the air to cause secondary oxidation, and at the same time, the protective slag thickness is maintained at 60 mm, to ensure the uniformity of lubrication and heat transfer, and indirectly inhibit the flange transverse crack; The long nozzle of the ladle adopts sealing ring + argon sealing protection, the argon flow rate of the ladle is 120 L / min, the immersion nozzle of the tundish is inserted to a depth of 80 mm, the superheat degree of the molten steel in the tundish is controlled to be 28℃, and the water flow rate control range of the BB1 section (575*450*110mm) of the mold is adjusted as follows: the inner and outer arc is 1820 L / min, the side arc is 1180 L / min, the amplitude is ±3mm, and the water temperature of the mold is controlled to be 42℃. The total specific water flow rate of the secondary cooling is 0.7 L / kg, which is controlled in five zones (50% in the first zone, 30% in the second zone, 28% in the third zone, 20% in the fourth zone, and 16% in the fifth zone), the specific water flow rate of the inner arc is 20% lower than that of the outer arc, the water flow rate of the nozzle is adjusted in real time in combination with the surface temperature field of the casting blank, so that the temperature gradient of the flange region is ≤20℃ / m; the water temperature of the secondary cooling is controlled to be 32℃, the constant casting speed 0.95 m / min is adopted in combination with the low cooling rate ≤1.5℃ / s, so that the flange temperature at the straightening section is 960℃; the molten steel weight in the tundish is 35 t, and the molten steel temperature in the tundish is 1539℃.

[0048] 3. Performance: The method is used for producing 12 heats in total and 1620 t in the BB1 section of the beam blank continuous casting machine, the nitrogen content of the 12 heats of the mold gas samples is 30 ppm at the maximum, 21 ppm at the minimum, and 25 ppm on average, the oxygen content is 28 ppm at the maximum, 20 ppm at the minimum, and 22 ppm on average.

[0049] All the casting blanks are subjected to slow cooling and finishing after landing, the finishing positions include the inner side of the flange and the web, there are 8 longitudinal cracks under the skin on the web, the length of the longitudinal cracks on the web is about 30-60 mm, and no transverse crack is found in the flange skinning finishing inspection.

[0050] The rolled material is detected for mechanical and process performance, the specification of the rolled material is H588*300*12*20mm, the average yield strength is 398Mpa, the average tensile strength is 570Mpa, the average elongation after fracture is 22%, and the average impact energy at-20℃ is 45J, which all meet the requirements.

[0051] The above only describes the preferred embodiments of the present application and is not used to limit the present application, the present application can have various modifications and changes for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method of suppressing transverse cracking of the flange of a niobium-containing steel strand, characterized in that, The method comprises the following steps: The chemical composition of the Nb-containing steel slab flange is adjusted to comprise the following components in mass percentage: C 0.08%-0.12%, Mn 1.4%-1.5%, Nb 0.03%-0.04%, Ti 0.008%-0.018%; The production process comprises: pretreatment desulfurization of molten iron, converter smelting, LF refining and continuous casting to obtain the Nb-containing steel slab flange; wherein, In the continuous casting process, the liquid level fluctuation range of the crystallizer is stabilized within ±3mm, high-basicity peritectic steel lithium-containing protective slag is used; the total specific water quantity of the water distribution system of the secondary cooling is controlled to be 0.6-0.8L / kg, weak cooling mode is used in the flange corresponding secondary cooling zone, the cooling temperature is controlled in five zones, which are: zone 1 50-55%, zone 2 25-27%, zone 3 20-25%, zone 4 15-22%, zone 5 10-15%; the specific water quantity of the inner arc is 15-20% lower than that of the outer arc, the nozzle water quantity is adjusted to make the temperature gradient of the flange region ≤20℃ / m; the secondary cooling water temperature is controlled to be 30-35℃; constant casting speed 0.95m / min is used to cooperate with low cooling rate ≤1.5℃ / s, so that the slab surface temperature is kept ≥920℃ in the straightening section, the tundish temperature is dynamically matched with the casting speed, and the casting speed is reduced by 0.02m / min for every 5℃ increase of the temperature.

2. The method of suppressing transverse cracking of the flange of a niobium-containing steel strand according to claim 1, characterized in that, The high-basicity peritectic steel lithium-containing protective slag comprises the following components in mass percentage: SiO2 22.03-24.06%, Al2O3 12.03-12.24%, Fe2O3 1.09-1.15%, CaO 34.47-34.99%, R 1.56-1.58%, Na2O 0.50-0.53%, F 4.08-4.10%, Li2O 0.4-0.45%, C 15.34-15.55%, H2O 0.33-0.34%; the melting point is 1275-1276℃, the melting speed is 43-44s, the bulk density is 0.71-0.73g / cm3, and the viscosity is 0.56-0.59Pa.S.

3. The method of suppressing transverse cracking of the flange of a niobium-containing steel strand according to claim 1, characterized by, The molten iron is pretreated and desulfurized to S≤0.008%, and the slag removal rate is ≥95%.

4. The method of suppressing transverse cracking of the flange of a niobium-containing steel strand according to claim 1, characterized by, In the converter smelting process, the end-point C content is controlled to be 0.05%-0.07%; the oxygen lance position adopts "high-high-low" oxygen lance position control mode, the initial high lance position range is 1800mm-1850mm, the medium-term high lance position range is 1450mm-1600mm, and the late low lance position range is 1000mm-1200mm; the end-point low lance position time is controlled to be ≥60s; the oxygen pressure during the oxygen blowing process is controlled to be 0.7MPa-1.0MPa; metal manganese, ferrosilicon, niobium iron and nickel plate are used for alloying, and are added uniformly when the molten steel is discharged to 1 / 4, and are added completely when the molten steel is discharged to 3 / 4, the alloy is added to the steel flow impact area, the steel discharge time is ≥3min, and the steel discharge temperature is 1630℃-1650℃.

5. The method of suppressing transverse cracking of the flange of a niobium-containing steel strand according to claim 1, wherein In the LF refining process, argon stirring is used throughout the process, argon flow rate is 100-200 L / min, argon purity is 99.99%; after the addition of recarburizer, adjust the argon flow rate to 800-1000 L / min, argon blowing for 2-5 min; entry temperature is 1554-1574℃, exit temperature is 1560-1578℃; soft argon blowing time is >12 min, 80-120 meters of calcium wire is fed before soft argon blowing per furnace, and the refining period is not less than 45 min.

6. The method of suppressing transverse cracking of the flange of a niobium-containing steel strand according to claim 1, characterized by, In the continuous casting process, the long nozzle of the ladle is protected by a sealing ring and argon sealing, and the argon flow rate of the ladle is controlled at 100-150 L / min; the immersion nozzle insertion depth of the tundish is controlled at 70-80 mm, and the tundish steel overheat is controlled at 15-28℃; the control range of the mold water volume is adjusted to: inner and outer arc 1800-1850 L / min, side arc 1100-1200 L / min, mold water temperature is controlled at 38-42℃, and the mold structure adopts curved copper plate design, and the uniformity of the wide surface heat flux density is improved by 20%.

7. The method of suppressing transverse cracking of the flange of a niobium-containing steel strand according to claim 1, wherein In the continuous casting process, the thickness of the high-alkali peritectic steel containing lithium in the mold is 50-60 mm, and the thickness of the liquid slag layer is 4-6 mm.